The Iteration Solution of Matrix Equation AXB=C Subject to a Linear Matrix Inequality Constraint - Na Huang; Changfeng Ma (Abstract and Applied Analysis)
We propose a feasible and effective iteration method to find solutions to the matrix equation AXB=C subject to a matrix inequality constraint DXE≥F, where DXE≥F means that the matrix DXE-F is nonnegative. And the global convergence results are obtained. Some numerical results are reported to illustrate the applicability of the method.